Urgensi Penerapan Etika Profesi Terhadap Upaya Penegakan Hukum di Indonesia - Salmanita Shalsabella Pramudita; Kayus Kayowuan Lewoleba (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Ethics is an assessment of whether someone's behavior or actions are right or wrong. Meanwhile, morality is the rightness or wrongness of human behavior. Ethics are ideas and ideals about the motives for moral action or behavior. As the author, I took the title: "The Urgency of Implementing Professional Ethics in Law Enforcement Efforts in Indonesia". We have great hope as writers that by writing this, we can provide benefits and knowledge to readers in accordance with its objectives. This research uses a normative juridical approach, namely by inventorying, studying and analyzing and understanding law as a set of regulations or positive norms in the legislative system that regulates human life. Professional ethics is an ethical attitude that is an integral part of facing life as a professional. Only professionals can or know better whether their behavior in carrying out their professional duties is in accordance with the ethical requirements of their profession.